Control of Citrus Post-harvest Green Molds, Blue Molds, and Sour Rot by the Cecropin A-Melittin Hybrid Peptide BP21 - Wang, Wenjun; Liu, Sha; Deng, Lili; Ming, Jian; Yao, Shixiang; Zeng, Kaifang (Frontiers in Microbiology, 2018)
In this study, the activity of the cecropin A-melittin hybrid peptide BP21 (Ac-FKLFKKILKVL-NH2) in controlling of citrus postharvest green and blue molds and sour rot and its involved mechanism was studied. The minimum inhibitory concentrations (MICs) of BP21 against Penicillium digitatum, Penicillium italicum and Geotrichum candidum were 8, 8, and 4 μmol L-1, respectively. BP21 could inhibit the growth of mycelia, the scanning electron microscopy (SEM) results clearly showed that the mycelia treated with BP21 shrank, formed a rough surface, became distorted and collapsed. Fluorescent staining with SYTOX Green (SG) indicated that BP21 could disintegrate membranes. Membrane permeability parameters, including extracellular conductivity, the leakage of potassium ions, and the release of cellular constituents, visibly increased as the BP21 concentration increased. Gross and irreversible damage to the cytoplasm and membranes was observed. There was a positive correlation between hemolytic activity and the concentration of BP21. These results suggest peptide BP21 could be used to control citrus postharvest diseases.